Short-term performance effects of high power, high force, or combined weight-training methods - Harris, G. H.; Stone, M. H.; O`Bryant, H. S.; Proulx, C. M.; Johnson, R. L. (The Journal of Strength and Conditioning Research, 2000)
Some controversy exists concerning the "transfer of training effect" from different methods of resistance-training programs to various athletic performance variables. The purpose of this study was to examine the effects of 3 different resistance-training methods on a variety of performance variables representing different portions of the force velocity curve, ranging from high force to high speed movements. Forty-two previously trained men (1 repetition maximum [RM] squat kg per kg body mass 1.4) served as subjects. After a 4-week high-volume training period and the pretests, the subjects were randomly assigned to 1 of 3 groups. The groups were high force (HF; n = 13), high power (HP; n = 16), and a combination training group (COM; n = 13); each group trained 4 d·wk1 for 9 weeks. Group HF trained using 80-85% of their 1RM values. Group HP trained at relative intensities approximating 30% of peak isometric force. Group COM used a combination training protocol. Variables measured pre- and posttraining were the 1RM parallel squat, 1RM 1/4 squat, 1RM midthigh pull, vertical jump (VJ), vertical jump power, Margaria-Kalamen power test (MK), 30-m sprint, 10-yd shuttle run (10-yd), and standing long jump (SLJ). Data were analyzed within groups with t-tests, and the between-group analysis used a group X trials analysis of variance test. The HF group improved significantly in 4 variables (p 0.05 for squat, 1/4 squat, midthigh pull, MK), the HP group in 5 variables (p 0.05 for 1/4 squat, midthigh pull, VJ, MK, SLJ), and the COM group in 7 variables (p 0.05 for squat, 1/4 squat, midthigh pull, VJ, VJP, 10-yd). These results indicate that when considering the improvement of a wide variety of athletic performance variables requiring strength, power, and speed, combination training produces superior results.